More evidence on cash transfers and child nutritional outcomes: A systematic review and meta-analysis - Manley, James; Alderman, Harold; Gentilini, Ugo (World Bank, 2022)
The good news from the nutrition community is that stunting and growth faltering is less common than ever before. The prevalence of stunting among children under 5 years declined by almost a third from 2000 to 2017, with Asia seeing a prevalence drop of over 40 percent, from 38 percent to 23 percent, and Latin America bringing stunting to under 10 percent of the population, a decline of 46 percent. Overall, stunting has tended to decline about 1 percent per year (Victora et al. 2021). However, the danger persists: even before COVID-19, the Sustainable Development Goals relating to nutrition were seen as unlikely to be reached.